Audio-visual integration through the parallel visual pathways - Kaposvári, Péter; Csete, Gergő; Bognár, Anna; Csibri, Péter; Tóth, Eszter; Szabó, Nikoletta; Vécsei, László; Sáry, Gyula; Tamás Kincses, Zsigmond (Brain research, 2015)
Audio-visual integration has been shown to be present in a wide range of different conditions, some of which are processed through the dorsal, and others through the ventral visual pathway. Whereas neuroimaging studies have revealed integration-related activity in the brain, there has been no imaging study of the possible role of segregated visual streams in audio-visual integration. We set out to determine how the different visual pathways participate in this communication. We investigated how audio-visual integration can be supported through the dorsal and ventral visual pathways during the double flash illusion. Low-contrast and chromatic isoluminant stimuli were used to drive preferably the dorsal and ventral pathways, respectively. In order to identify the anatomical substrates of the audio-visual interaction in the two conditions, the psychophysical results were correlated with the white matter integrity as measured by diffusion tensor imaging.The psychophysiological data revealed a robust double flash illusion in both conditions. A correlation between the psychophysical results and local fractional anisotropy was found in the occipito-parietal white matter in the low-contrast condition, while a similar correlation was found in the infero-temporal white matter in the chromatic isoluminant condition. Our results indicate that both of the parallel visual pathways may play a role in the audio-visual interaction.
Keywords: Imaging, Three-Dimensional; sluchová percepce; White Matter; Humans; MRI; mapování mozku; Multisensory; DTI; Visual Pathways; Acoustic Stimulation; Female; dospělí; zraková percepce; Auditory Perception; TBSS; lidé; Photic Stimulation; Visual Perception; světelná stimulace; bílá hmota; zobrazování difuzních tenzorů; Signal Detection, Psychological; Brain Mapping; Adult; anizotropie; ženské pohlaví; Diffusion Tensor Imaging; Male; zrakové dráhy; zobrazování trojrozměrné; mužské pohlaví; Anisotropy; teorie detekce signálu; Doubleflash; akustická stimulace